Pengaruh Praktik Manajemen Rantai Pasok terhadap Keunggulan Kompetitif dan Kinerja Agroindustri Obat Tradisional dan Rempah Lokal Madura - Elfira Maya Adiba; Lilis Suaibah; Fajar Ramadhan (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to: analyse the effect of supply chain management practices on the competitive advantage of local Madura traditional medicinal and spice products; explore the influence of supply chain management practices on the performance of the local Madura traditional medicine and spice agroindustry; investigate the effect of competitive advantage on the performance of the local Madura traditional medicine and spice agroindustry. The population in this study were entrepreneurs of traditional Madurese medicines and local spices. The sampling technique in this study used purposive sampling with a total sample of 25. The data collection technique used a questionnaire tested for validity and reliability. The data analysis tool used to answer the research hypothesis is SmartPLS. The results of this study indicate that: supply chain management practices have a direct and positive effect on the competitive advantage of traditional Madurese medicinal products and local spices; supply chain management practices have an immediate and positive impact on the performance of the Madura traditional medicine and local spice agroindustry; the competitive advantage of conventional Madurese medicinal products and local spices has a direct and positive effect on the performance of SMEs. Agro-industry SMEs are advised to continue increasing their competitive advantage and supply chain management to continue developing their business.